Step-by-step explanation:
9.(12/3)²
9.(144/9)
[The 9 in numerator and the 9 in denominator can be cancelled]
144
the answer is 144
Please mark me as brainliest
Answer:
![\sqrt{1314}](https://tex.z-dn.net/?f=%20%5Csqrt%7B1314%7D%20)
Step-by-step explanation:
a²+b²=c² so: 33²+15²=x²
1089+225=x²
1314=x²
take the square root of both sides
36.249=x or
![\sqrt{1314 }](https://tex.z-dn.net/?f=%20%5Csqrt%7B1314%20%7D%20)
=x
Answer:
2(4x + 1)(x + 1)
Step-by-step explanation:
Given
8x² + 10x + 2 ← factor out 2 from each term
= 2(4x² + 5x + 1)
To factor the quadratic
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term
product = 4 × 1 = 4 and sum = + 5
The factors are + 1 and + 4
Use these factors to split the x - term
4x² + x + 4x + 1 ( factor the first/second and third/fourth terms )
= x(4x + 1) + 1 (4x + 1) ← factor out (4x + 1)
= (4x + 1)(x + 1), thus
4x² + 5x + 1 = (4x + 1)(x + 1) and
8x² + 10x + 2 = 2(4x + 1)(x + 1) ← in factored form
Answer:
x = 10/3
, y = 0
Step-by-step explanation:
Solve the following system:
{4.5 x - 2 y = 15
3 x - y = 10
In the first equation, look to solve for x:
{4.5 x - 2 y = 15
3 x - y = 10
4.5 x - 2 y = (9 x)/2 - 2 y:
(9 x)/2 - 2 y = 15
Add 2 y to both sides:
{(9 x)/2 = 2 y + 15
3 x - y = 10
Multiply both sides by 2/9:
{x = (4 y)/9 + 10/3
3 x - y = 10
Substitute x = (4 y)/9 + 10/3 into the second equation:
{x = (4 y)/9 + 10/3
3 ((4 y)/9 + 10/3) - y = 10
3 ((4 y)/9 + 10/3) - y = ((4 y)/3 + 10) - y = y/3 + 10:
{x = (4 y)/9 + 10/3
y/3 + 10 = 10
In the second equation, look to solve for y:
{x = (4 y)/9 + 10/3
y/3 + 10 = 10
Subtract 10 from both sides:
{x = (4 y)/9 + 10/3
y/3 = 0
Multiply both sides by 3:
{x = (4 y)/9 + 10/3
y = 0
Substitute y = 0 into the first equation:
Answer: {x = 10/3
, y = 0